RACS: A referee anti-cheat scheme for P2P gaming - Webb, Steven; Soh, Sieteng; Lau, William (Association for Computing Machinery (ACM), 2007)
Peer-to-peer (P2P) architectures provide better scalability than Client/Server (C/S) for Massively Multiplayer Online Games (MMOG); however, they increase the possibility of cheating. Existing P2P cheat solutions only prevent protocol level cheats, ignoring two prevalent forms of cheating: information exposure (IE) and invalid commands (IC). This paper proposes the Referee Anti Cheat Scheme (RACS), a hybrid between P2P and C/S. As in P2P, RACS allows peers to exchange updates directly, improving its scalability. However, similar to the server in C/S, the referee in RACS has authority over the game state, providing cheat resistance equal to that in C/S. This paper describes how RACS prevents cheating including IE and IC. Our simulation and analysis show that the average bandwidth and delay in RACS is lower than that in P2P and C/S. This paper also includes a case study of integrating RACS with a commercial network game architecture.